LIKEN AMILOIDOSIS - Nanda Chairina; Wizar Putri Mellaratna (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Amyloidosis is a term for various groups of diseases with lots of amyloid protein in organs and/or tissues, causing disease. In this condition, amyloid protein is deposited in the dermis layer of the skin which is called lichen amyloidosis. Lichen amyloidosis is the most common type of cutaneous amyloidosis. The prevalence of cutaneous amyloidosis is relatively rare, only 0.2-0.3%. It is chronic in nature which usually appears later in life. This article discusses a case of a 39-year-old female patient who came with complaints of spots on both sides accompanied by itching. These complaints have been experienced since ± 2 years ago and are felt to be getting worse in the last few months. Previously the patient had used a type of topical medication obtained from the local puskesmas, but there was no improvement. Examination of the general status found the general condition of the patient looked moderately ill, conscious awareness, vital signs within normal limits. Dermatological status obtained efflorescence in the form of macules to multiple papules with hyperpigmentation, well defined, discrete available, accompanied by scaling and lichenification. Patients were treated with oral corticosteroids (methylprednisolone), topical corticosteroids (desoximethasone) and salicylic acid. Patients are also educated to avoid scratching and rubbing on the lesions. The patient showed thinning lesions after 7 days of therapy.